Ouvidoria em órgão regulador do sistema financeiro nacional: o caso do Banco Central do Brasil - Santos, André Barros (2008)
This study aims to understand how can the Ombudsman Office in the Central Bank of Brazil - the national monetary policy authority - contribute towards its interaction with society, especially regarding its customer service center. Social control over the government appears to be vital to the governments be responsive and pursue the public interest. The Ombudsman Office can be one instrument of social control. This research is a case study. The study presents the term ombudsman in the world and also its equivalent in Brazil - 'ouvidor'. Next, concepts related to public administration and accountability are approached. It was verified that the Ombudsman office can be effective in helping the social control of Central Bank of Brazil. Moreover, the Ombudsman Office brings a lot of valuable knowledge to this organization, mainly regarding its social role and its internal processes.